2006
DOI: 10.1080/00420980600838184
|View full text |Cite
|
Sign up to set email alerts
|

Power Relations in Urban Decision-making: Neo-liberalism, 'Techno-politicians' and Authoritarian Redevelopment in Santiago, Chile

Abstract: Taking as a subject of study an on-going urban development project in Santiago, Chile, the paper interprets how public and private actors came together in an urban decision-making episode which represented a particular power configuration. To consider both the structural forms of constraint and the differential capacity of actors to exert power, an analytical framework is constructed, derived from Giddens' structuration theory and from Foucault's approach to power. The analysis of the specific relationships es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 44 publications
0
24
0
13
Order By: Relevance
“…Swyngedouw, ). In the context of Pinochet's military dictatorship (1973–1989), a consensus‐oriented model of governing was established, forced by political and economic elite networks and a technocratic political guiding principle (Zunino, ). At the time, Chile became a neoliberal laboratory characterized by thorough processes of liberalization and privatization of urban development.…”
Section: Political Opportunity Structures and Conflict Triggers In Pementioning
confidence: 99%
“…Swyngedouw, ). In the context of Pinochet's military dictatorship (1973–1989), a consensus‐oriented model of governing was established, forced by political and economic elite networks and a technocratic political guiding principle (Zunino, ). At the time, Chile became a neoliberal laboratory characterized by thorough processes of liberalization and privatization of urban development.…”
Section: Political Opportunity Structures and Conflict Triggers In Pementioning
confidence: 99%
“…This UK study concluded that although the notion of partnerships creates a vision of public policy in which everyone seems to benefit by emphasizing efficiency, devolution, and participation, the reality is different: partnerships failed to be inclusive of representative interests; they have reinforced the influence of the central government and facilitated the participation of the private sector in the delivery of public services. The differential capacity of actors to exert power in urban renewal and decision-making has been studied in the context of Santiago, Chile 49. In this situation, it was found that representatives from the central government and private investors controlled local redevelopment, while the local government and the people living near the urban renewal project ended up in non-influential positions.…”
Section: Key Elements Of Urban Governance For Health Equitymentioning
confidence: 99%
“…El método de organización seguido actualmente es la realización de asambleas comunales en las cuales la directiva asume un rol de coordinación, información y canalización de las propuestas surgidas de la asamblea, a su vez que la asamblea tiene la facultad para aprobar o desaprobar las propuestas originadas desde la directiva. Las asambleas se realizan con una frecuencia de 3 17 Ver Zunino, 2006;Zunino e Hidalgo, 2009. in the words of Putnam (1983) En tercer lugar, y concordante con nuestra primera inferencia, los dirigentes vecinales destacan lo positivo que resulta residir en una ciudad-balneario y que los atributos funcionales de la ciudad tienden a aminorar las carencias materiales o los problemas que discutiremos en la siguiente sub-sección. Se colige que los pobladores no se sienten atrapados en un gueto, sino se consideran parte integrante de la ciudad de Pucón.…”
Section: Satisfacción Residencialunclassified